PRE-CONSCRIPTION MILITARY TRAINING OF THE STUDENT IN THE DIRECTION OF THE COUNTRY, THE IDEA OF PEACE SMALL FORM METHODS AND TOOLS - Abdullayev Ixtiyor (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
As it is known, performed based on certain methods of work experience in various fields of science. Her research research methods the scientific aspects of the organization, in order to ensure the effectiveness of the methods used by researchers maj is listed. Pre-conscription military training of the student in the direction of the idea of peace in the country following the formation of the scientific-pedagogical methods led to the effective use of: pedagogical observation, survey, interview, interview, show (presentation), modeling, mathematical-statistical analysis.